PERSONALITY SAFETY IN STUDENT’S STRUCTURE OF SOCIAL MATURITY: THE THEORETICAL AND EMPIRICAL EXPLICATION - Virna, Zhanna; Lazorko, Olga; Pustovoit, Miroslava (PSYCHOLOGICAL JOURNAL, 2019)
The main categorical and conceptual outlines of the phenomenon of personality safety from the standpoint of the systemic, integrative, subjective and activity approaches are detailed. The systemic and structural peculiarities of personality safety organization as a psychological formation, providing acquisition and support of human psychological comfort, are revealed. The theoretical model of the structural organization of a person’s social maturity is developed, which include the following components: value-semantic, emotional-evaluative and regulatory-behavioural. The consideration of specific features of personality safety for each social maturity component (a person’s individual senses that divides the phenomena of surrounding reality by their safety or danger, a person’s internal harmony, willingness to take risks) is concentrated around the psychological content of a person’s resource potential for his/her personality safety as the person’s social and psychological activity and the corresponding development of his/her value-semantic sphere, emotional and motivational orientation and ability to comprehension, adaptation and control over a situation. The research results show that the social maturity structural components of students in technical and humanitarian specialties (group 1) and students of “risky” professions (group 2) are rather dynamic and have significant differences. The specifics and manifestations of the resource potential of personality safety in students’ structure of social maturity are substantiated. The resource potential of such personality safety component as an emotional balance characteristic for students in technical and humanitarian specialties was empirically verified; here, the functional plane of emotions takes the form of emotional balance that perform regulatory mobilization at interactions with the environment. The resource potential of such personality safety component as behavioural normative of students in risky specialties demonstrates the specific functional plane of their behavioural activities in the form of behavioural self-regulation and adaptive manifestations of their value orientations as for their life and professional self-fulfilment. We specify that the full expression of the resource potential of personality safety integrates emotional and behavioural attitudes through awareness on their constituent characteristics, which makes it possible not only to change the reality but also oneself with adaptation to new objective peculiarities with the help of new interpretative models of consciousness.